Implementation of Genetic Algorithm to Solve Travelling Salesman Problem with Time Window (TSP-TW) for Scheduling Tourist Destinations in Malang City - Yuliastuti, Gusti Eka; Mahmudy, Wayan Firdaus; Rizki, Agung Mustika (Faculty of Computer Science (FILKOM) Brawijaya University, 2017)
In doing travel to some destinantions, tourist certainly want to be able to visit many destinations with the optimal scheduling so that necessary in finding the best route and not wasting lots of time travel. Several studies have addressed the problem but does not consider other factor which is very important that is the operating hours of each destination or hereinafter referred as the time window. Genetic algorithm proved able to resolve this travelling salesman problem with time window constraints. Based on test results obtained solutions with the fitness value of 0,9856 at the time of generation of 800 and the other test result obtained solution with the fitness value of 0,9621 at the time of the combination CR=0,7 MR=0,3.